New Galumnidae (Acari, Oribatida) from the Merida and Zulia States, Venezuela - Ermilov, Sergey G. (Zootaxa, 2024)
Three new species of the family Galumnidae (Oribatida)—Sacculogalumna zuliaensis sp. nov., Pergalumna (Pergalumna) convergens sp. nov. and Carinogalumna meridaensis sp. nov.—are described, based on adults collected from cloud forest in the Merida State, Western Venezuela, and pasture meadow in the Zulia State, Northwestern Venezuela. The genera Sacculogalumna and Carinogalumna are registered in the Venezuelan fauna for the first time. Identification keys to the known species of Sacculogalumna and Carinogalumna are provided.